Power-efficient methods of de-icing of power line's wires; XXXII. Kandó Konferencia 2016. Kandó a tudomány hajóján - Dementiev Yu. N. Yuriy Nikolaevich; Negodin K. N. Kirill Nikolaevich; Sukhorukov S. I. Sergey I.; Solovyev S. V. Sergey Viktorovich (Automation Section, 2016)
Title screen